Resilience and life cycle assessment of ion exchange process for ammonium removal from municipal wastewater - Guida, Samuela; Conzelmann, Lea; Remy, Christian; Vale, Peter C. J.; Jefferson, Bruce; Soares, Ana (Elsevier, 2021)
This study was completed to understand the resilience of an ion exchange (IEX) process for its ability to remove variable ammonium (NH4+-N) loads) and to prove its environmental benefits through a life cycle assessment (LCA). The tertiary 10 m3/day demonstration scale IEX was fed with variable NH4+-N concentrations (<0.006-26 mg NH4+-N /L) naturally found in municipal wastewater. Zeolite-N was used as ion exchange media and regeneration was completed with 10% potassium chloride (KCl). The influent NH4+-N concentration impacted the ion exchange capacity, which ranged from 0.9-17.7 mg NH4+-N/g media. When the influent concentration was <2.5 mg NH4+-N/L, the Zeolite-N released NH4+-N (up to 12%). However, the exchange increased up to 62% when the influent NH4+-N load peaked, confirming the resilience of the process. A 94% regeneration efficiency was obtained with fresh regenerant, however, with the increase of the mass of NH4+-N on the media, the regeneration efficiency decreased. An optimisation of the volume of brine and regeneration contact time is suggested. To further measure the benefits of the IEX process, an LCA was conducted, for a 10,000 population equivalent reference scenario, and compared with traditional nitrification-denitrification WWTP. The LCA revealed that IEX with regenerant re-use and NH4+-N recovery through a membrane stripping process resulted in reductions of: 25% cumulative energy demand; 66% global warming potential and 62% marine eutrophication potential, when compared to traditional WWTP. This work demonstrated that the IEX process is an efficient and an environmentally benign technology that can be widely applied in WWTPs
Keywords: Net-zero targets; circular economy; synthetic zeolite; nutrients; ammonia recovery; Ammonia removal